2017
DOI: 10.1016/j.ymthe.2017.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral Cascade-Targeting Ligand for IL-6 Receptor-Mediated Gene Delivery to Glioma

Abstract: The effective treatment of glioma is largely hindered by the poor transfer of drug delivery systems across the blood-brain barrier (BBB) and the difficulty in distinguishing healthy and tumorous cells. In this work, for the first time, an interleukin-6 receptor binding IP peptide was exploited as a cascade-targeting ligand in combination with a succinoyl tetraethylene pentamine (Stp)-histidine oligomer-based nonviral gene delivery system (IP-Stp-His/DNA). The IP peptide provides multiple functions, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…Once accumulated at tumor sites, specific binding with target tumor cells and subsequent effective cellular internalization can be facilitated by incorporated targeting functions. For example, targeting ligands such as B6 [ 109 , 143 ], cRGD [ 143 ], folic acid (FolA) [ 109 , 113 ], methotrexate (MTX) [ 144 ], c-Met-binding peptide (cMBP2) [ 114 , 115 ], transferrin (Tf), AP-1, EGF receptor-binding peptide (GE11) [ 143 ] and IL-6 receptor binding I6P7 peptide [ 145 ] were attached to precise PEG shielding domains and then introduced to the surface of polyplexes by pre- or post-modification for active receptor-mediated accumulation in target tumor cells.…”
Section: Pharmacological Barriers For In Vivo Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Once accumulated at tumor sites, specific binding with target tumor cells and subsequent effective cellular internalization can be facilitated by incorporated targeting functions. For example, targeting ligands such as B6 [ 109 , 143 ], cRGD [ 143 ], folic acid (FolA) [ 109 , 113 ], methotrexate (MTX) [ 144 ], c-Met-binding peptide (cMBP2) [ 114 , 115 ], transferrin (Tf), AP-1, EGF receptor-binding peptide (GE11) [ 143 ] and IL-6 receptor binding I6P7 peptide [ 145 ] were attached to precise PEG shielding domains and then introduced to the surface of polyplexes by pre- or post-modification for active receptor-mediated accumulation in target tumor cells.…”
Section: Pharmacological Barriers For In Vivo Deliverymentioning
confidence: 99%
“…In case of the all-in-one formulations with targeting and shielding domains ( Figure 5 A), pDNA polyplexes formed by 2-arm/4-arm ligand-PEG-OAAs exhibited an average size of ~100 nm, and the histidine-incorporation in the backbone significantly improved the pDNA transfection efficiency as compared to those control groups with alanine in the backbone, or than to the corresponding non-targeted groups [ 140 , 146 , 147 ]. After intravenous injection of I6P7-PEG-Stp-histidine/pDNA polyplexes developed by Huang et al [ 145 ], the delivered pING4 (pDNA encoding inhibitor of growth 4) was found successfully expressed in the glioma, resulting in a significantly prolonged survival time of treated orthotopic U87-bearing mice. As for much smaller siRNA, 2-arm/4-arm ligand-PEG-OAAs [ 140 , 146 , 147 ] formed multifunctional nanoplexes with an average size as small as ~8 nm.…”
Section: Pharmacological Barriers For In Vivo Deliverymentioning
confidence: 99%
“…Based on these facts, upregulation and supplement of ING4 has been raised as a possible way of treating brain tumors. Recently, Wang et al . and Yao et al .…”
Section: Therapeutic Genes For Cns Diseasesmentioning
confidence: 99%
“…The DGL‐PEG‐LNP/DNA nanoparticles were shown to possess excellent BBB‐crossing efficiency and an anti‐glioma effect both in vitro and in vivo . In the other study, an interleukin‐6 receptor binding I 6 P 7 peptide was developed to covalently attach a succinoyl tetraethylene pentamine (Stp)‐histidine oligomer as a gene vector to encapsulate pING4 (I 6 P 7 ‐Stp‐His/pING4 nanoparticles) (Figure ). The results obtained showed that I 6 P 7 peptide‐modified nanoparticles could cross the BBB and accumulate in glioma effectively via mediation of interleukin‐6 receptors.…”
Section: Therapeutic Genes For Cns Diseasesmentioning
confidence: 99%
See 1 more Smart Citation